Environmental impacts generated by road construction and operation (Research, Society and Development, 2019)
Shedding production is the dominant factor at the time of planning the construction of a highway. Transferring products from one corner to another is the goal of globalization that gives anyone a product regardless of where they are located in the world. However, it is not possible to carry out this transit by air or water in most cases. By the disposition of the continents and the high prices of the air cargo transport to send products by land is more attractive whenever possible. In this way, more roads means less cost, more practicality and speed in the delivery of goods. However, building and operating a highway requires a lot of care, especially with the environment and road quality. This paper presents the characteristics of the roads in Brazil, the expansion process and the challenges faced for the construction and operation of highways. An excerpt was selected in the state of Minas Gerais between the municipalities of Águas Formosas and Novo Oriente de Minas and raised the positive and negative social, environmental and structural impacts that occurred during the construction, paving and operation of the section called highway MG-409 e MG -105.